Pendampingan Minat dan Bakat Santri TPQ Ad-Adawam Melalui Program Ekstrakurikuler Pondok Romadlon di Desa Semen, Kecamatan Paron, Kabupaten Ngawi - Ubaidillah, M. Abi Mahrus; Dian Erwanto; Moch. Nurcholis; Moh. Tamim Ngizamul Ngulya; Muhammad Rizky Gymnastiar; Muhamad Maftuh; M. Nidhom Fahmi; Ahmad Azky Asfiya’; Muhammad Khoirin Najah; Muhammad Umar Taufiq (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2025)
The development of students' interests and talents at TPA/TPQ Ad Adawam, Semen Village, is a vital element in fostering a high-quality and competitive generation. This study highlights the importance of a systematic mentoring approach in exploring students' potential, covering aspects of character development, skills, and self-confidence. Despite challenges such as limited resources and a lack of experienced educators, the program aims to create a positive and inspiring learning environment. The research employs the ABCD (Asset-Based Community Development) approach, consisting of five stages: Discovery, Dream, Design, Define, and Destiny. Through these stages, students are guided to identify and plan their future based on their respective interests and talents. The results of the program indicate an increase in student participation in extracurricular activities, particularly in areas such as calligraphy, adhan (Islamic call to prayer), and public speaking. The success of the program is supported by competent educators, relevant curricula, and community involvement. These findings affirm that the development of students' interests and talents brings benefits not only on an individual level but also positively impacts the community by shaping a generation better prepared for future challenges.